2020
DOI: 10.3847/1538-4357/ab5db7
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dynamical Analysis of 0.1 pc Cores and Filaments in the 30 Doradus-10 Giant Molecular Cloud

Abstract: High-resolution (<0.1 pc) ALMA observations of the 30Dor-10 molecular cloud 15 pc north of R136 are presented. The 12 CO 2-1 emission morphology contains clumps near the locations of known midinfrared massive protostars, as well as a series of parsec-long filaments oriented almost directly towards R136. There is elevated kinetic energy (linewidths at a given size scale) in 30Dor-10 compared to other LMC and Galactic star formation regions, consistent with large scale energy injection to the region. Analysis of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…In contrast to the stellar population and PMS/YSO studies, available molecular gas maps of the 30 Dor region have much poorer angular resolution (10 pc; Johansson et al 1998;Minamidani et al 2008;Wong et al 2011;Kalari et al 2018;Okada et al 2019), aside from previously published data from the Atacama Large Millimeter/submillimeter Array (ALMA) covering a relatively small (12 × 12 pc) area (Indebetouw et al 2013(Indebetouw et al , 2020. To address these limitations, we have conducted new observations with ALMA, exploiting the array's unique capability to obtain a sensitive, high-resolution (1 75 beam) map of the giant molecular cloud complex across an extent of ∼100 pc using the CO J = 2-1 and 13 CO J = 2-1 transitions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the stellar population and PMS/YSO studies, available molecular gas maps of the 30 Dor region have much poorer angular resolution (10 pc; Johansson et al 1998;Minamidani et al 2008;Wong et al 2011;Kalari et al 2018;Okada et al 2019), aside from previously published data from the Atacama Large Millimeter/submillimeter Array (ALMA) covering a relatively small (12 × 12 pc) area (Indebetouw et al 2013(Indebetouw et al , 2020. To address these limitations, we have conducted new observations with ALMA, exploiting the array's unique capability to obtain a sensitive, high-resolution (1 75 beam) map of the giant molecular cloud complex across an extent of ∼100 pc using the CO J = 2-1 and 13 CO J = 2-1 transitions.…”
Section: Introductionmentioning
confidence: 99%
“…The mass estimate when using the (1-0) lines is higher than our fitted RADEX (by an average factor of 1.66±0.19), which is harder to explain though not unprecedented (Indebetouw et al 2020). One way this could happen is if the 12 CO is not actually optically thick, which would make the LTE T ex estimate too low and shift the optical depth estimate higher.…”
Section: Lte Methodsmentioning
confidence: 61%
“…However, these calculations break down if 12 CO becomes optically thin, or if either line's level population is not well described by a Boltzmann distribution. Studies have shown regimes in which the LTE calculations overestimate the column density by up to a factor of two in bright (T B > 40 K) clouds (Indebetouw et al 2020), and underestimate the mass by up to a factor of 7 when the 13 CO becomes sub-thermally excited (Castets et al 1990;Padoan et al 2000;Heyer & Dame 2015). Assuming LTE also requires that the density is sufficiently high such that the excitation is entirely governed by temperature, meaning that any dependence on density drops out of the equations and so cannot be solved for.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, this situation has begun to change (with a handful of exceptions, e.g. Hamedani Golshan et al 2021;Sewilo 2021;Shimonishi et al 2021;Indebetouw et al 2020, describing observations of molecular cores in the Magellanic Clouds). Further afield, ALMA (Atacama Large Millimeter Array) and 𝐻𝑆𝑇 (Hubble Space Telescope), respectively, now allow us to image the high resolution (1 ≈ 50 pc at 10 Mpc) distribution of the molecular ISM at GMC scales across entire galaxies and (in the same targets) allow us to inventory clusters and luminous stars an order of magnitude in size smaller yet.…”
Section: Introductionmentioning
confidence: 99%